Return to sports activity following combined reconstructionof anterior cruciate ligament and anterolateral ligament (Journal of Health Sciences, 2025)
Introduction: Anterior cruciate ligament (ACL) injuries are increasingly common among young people, especially active athletes. This study aims to retrospectively assess long-term results following ACL and anterolateral ligament (ALL) reconstruction, with a focus on rehabilitation, return to sports activities, patient satisfaction, and the impact of ALL and ACL injury on the s’ daily life and sports activities.Methods: The study included 140 patients treated at the Day Surgery Unit of the “Sveti Duh” Clinical Hospital. All participants underwent ACL and ALL reconstruction.Results: The median Lysholm score for respondents with combined ALL and ACL injuries was 72 (range 8-100), compared to 79 (range 36-100) for those with isolated ACL injuries. A total of 63.6% of respondents resumed their sport after surgery and rehabilitation, while 5% completely ceased participation. The ACL-return to sport after injury scores, which measure the psychological response after injury, indicated no significant differences in psychological readiness to return to sports depending on the type of injury. Overall, 62.9% percent of respondents were fully satisfied with their rehabilitation outcomes, while 3.6% expressed limited satisfaction.Conclusion: Although knee function was significantly impaired in patients with combined ACL and ALL injuries, 62.9% of all respondents reported being satisfied with their rehabilitation outcomes. Among those with combined injuries, 36.4% expressed confidence in returning to their pre-injury level of athletic activity.